Effect of natural fibers reinforcement of honeycomb sandwich using numerical analysis - Muhammad Zulkarnain; Tofrowaih, Khairul Amri; Ariyanti, Silvi (Faculty of Engineering, Universitas Indonesia, 2022)
The honeycomb sandwich structure has been extensively investigated for its mechanical performance. Modification in improving such mechanical properties is an innovation required of honeycomb sandwich, especially with adding a random fibers reinforcement inside a sheet panel plate. This study was developed random fiber reinforcement using natural fiber of Oil Palm, Sugar Cane and Coconut which constructed by commercial software code of MATLAB. This investigation was analyzed the performance of three-point bending behavior by using the finite-element model which provides four levels fiber condition to observed: 0, 50, 100 and 150 fiber numbers. Ansys Workbench/Dynamic code was chosen to predict mechanical performance such as stress and displacement analysis. In fiber development study, a series of numerical simulations were carried out with 2 types of fiber orientation as reinforcement, unidirectional and chopped randomly. The hybrid orientation also implemented in this research by combined unidirectional and chopped fiber which was fixed at 150 numbers then varied in three sets: S50/C100, S100:C50, and S75/C75. As a result, it was confirmed that the fiber reinforcement enhances the stiffness of the structure, which contributes a lot to the promotion of the bending resistance capacity and energy absorption. Especially on unidirectional fiber orientation shown a significant increase in absorbing stress during testing. It was similar which reported by the hybrid system, the fiber reinforcement sandwich showed better mechanical behavior in the simulation, and it was influenced by the unidirectional orientation.